Identifying short surface ligands on metal phosphide quantum dots - Baquero, Edwin A. (Royal Society of Chemistry, 2016)

(untitled) (Phys Chem Chem Phys)
The control and understanding of the chemical and physical properties of quantum dots (QDs) demands detailed surface characterization. However, probing the immediate interface between the inorganic core and the ligands is still a major challenge. Here we show that using cross-polarization magic angle spinning (MAS) NMR, unprecedented information can be obtained on the surface ligands of Cd(3)P(2) and InP QDs. The resonances of fragments which are usually challenging to detect like methylene or methyl near the surface, can be observed with our approach. Moreover, ligands such as hydroxyl and ethoxide which have so far never been detected at the surface can be unambiguously identified. This NMR approach is versatile, applicable to any phosphides and highly sensitive since it remains effective for identifying quantities as low as a few percent of surface atoms.